2004
DOI: 10.1614/wt-03-142r2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Separate and Combined Applications of Herbicides on Weed Control and Yield of Sugar Beet

Abstract: Field studies were conducted to investigate the effects of different rates of herbicides on weed control, agronomic characteristics, and quality of sugar beet at Shiraz, Iran, in 2000 and 2001. Separate and combined applications of herbicides, including 14 combinations and different rates of grass and broadleaf herbicides, at two rates were used. Herbicides reduced weed biomass compared with the weedy check. In both years, maximum reduction in weed biomass was observed with desmedipham plus phenmedipham plus e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 13 publications
2
9
0
Order By: Relevance
“…Individual sugar beet herbicides seldom have a wide enough weed control spectrum or sufficient residual activity to control all weeds (Abdollahi, Ghardiri, 2004). The optimization of herbicide application in the sugar beet protection system can be achieved by using mixtures of appropriate components and their selected doses (Strandberg et al, 2005;Domaradzki, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Individual sugar beet herbicides seldom have a wide enough weed control spectrum or sufficient residual activity to control all weeds (Abdollahi, Ghardiri, 2004). The optimization of herbicide application in the sugar beet protection system can be achieved by using mixtures of appropriate components and their selected doses (Strandberg et al, 2005;Domaradzki, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Main reasons include slow early growth of sugar beet, its very low competitive ability at the beginning of vegetation, high sensitivity to herbicides (mainly in early growth stages), and also high cost of special herbicides. Moreover, using herbicides in sugar beet usually induced a decrease of root yield, even in the cases when visual symptoms of injury are not evident (Abdollahi and Ghadiri 2004).…”
mentioning
confidence: 99%
“…Fennimore and Rachuy (2005) reported that desmedipham/ phenmedipham and ethofumesate applications provided acceptable control of P. oleracea and A. retroflexus. Starke and Renner (1996); Bosak et al, (2001) and Abdollahi and Ghadiri (2004) reported that phenmedipham plus desmedipham showed a much better weeds control in sugar beet than phenmedipham alone. The reason for discrepancies among EDx value of herbicides could be ascribed to the different phenological stages of a plant, climatic conditions and plant species and the period of treatment.…”
Section: Discussionmentioning
confidence: 99%